Impact of COVID-19 on patient and healthcare professional attitudes, beliefs, and behaviors toward the healthcare system and on the dynamics of the healthcare pathway - Katarzyna Bernacki; Angie Keister; Nadia Sapiro; Jin Su Joo; Lisa Mattle (BMC, 2021)
Abstract Background COVID-19 has dramatically changed how healthcare is delivered and experienced. Methods One-on-one interviews and a virtual ethnographic roundtable were conducted among 45 patients, caregivers, and healthcare professionals (HCPs) in 4 therapeutic areas from the United States and Japan: overactive bladder, vasomotor symptoms, prostate cancer, and metastatic urothelial carcinoma. The goal was to identify the impact of COVID-19 on patient/caregiver and HCP attitudes, interactions, beliefs, and behaviors toward the healthcare system and care pathway. Results Four foundational themes were identified: 1) COVID-19 risk is relative; 2) isolation is collateral damage; 3) telehealth is a parallel universe; and 4) COVID-19 is destabilizing the foundations of healthcare. Numerous insights, influenced by diverse cultural, social, and psychological factors, were identified within each theme. Conclusions The impacts of COVID-19 were noticeable at multiple points of care during the "universal" care pathway, including at initial screening, referral to specialists, diagnosis, treatment initiation/surgery, and during ongoing care. Greater appreciation of the short- and long-term impacts of COVID-19 and resulting gaps in care may act as a catalyst for positive change in future patient care.